2021
DOI: 10.3389/fpls.2021.669064
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Herbarium Specimen Characteristics on Short-Read NGS Sequencing Success in Nearly 8000 Specimens: Old, Degraded Samples Have Lower DNA Yields but Consistent Sequencing Success

Abstract: Phylogenetic datasets are now commonly generated using short-read sequencing technologies unhampered by degraded DNA, such as that often extracted from herbarium specimens. The compatibility of these methods with herbarium specimens has precipitated an increase in broad sampling of herbarium specimens for inclusion in phylogenetic studies. Understanding which sample characteristics are predictive of sequencing success can guide researchers in the selection of tissues and specimens most likely to yield good res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…This method offers several important advantages over full genome sequencing and other modern sequencing methods, notably a combination of broad taxonomic application with high efficiency on non-model species, broad phylogenetic informativeness at both deep and shallow nodes, and cost-efficiency (Lemmon and Lemmon 2013). Because the method relies on short DNA sequences (200-400 bp), may work with very low DNA starting amount (down to 5 ng), and is rather insensitive to DNA degradation, it is also ideally suited to work with (up to centuries-old) material from natural history museums, allowing access to rare and previously ‘locked’ specimens (Särkinen et al 2012; Hart et al 2016; Brewer et al 2019; Forrest et al 2019; Alsos et al 2020; Bakker et al 2020; Folk et al 2021; Kates et al 2021). In addition, target capture sequencing of leaves generates a considerable sequence bycatch in the form of off-target reads (‘genome skimming’) that represent a wealth of chloroplast genes, allowing simultaneous reconstruction of the plastome (Weitemier et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This method offers several important advantages over full genome sequencing and other modern sequencing methods, notably a combination of broad taxonomic application with high efficiency on non-model species, broad phylogenetic informativeness at both deep and shallow nodes, and cost-efficiency (Lemmon and Lemmon 2013). Because the method relies on short DNA sequences (200-400 bp), may work with very low DNA starting amount (down to 5 ng), and is rather insensitive to DNA degradation, it is also ideally suited to work with (up to centuries-old) material from natural history museums, allowing access to rare and previously ‘locked’ specimens (Särkinen et al 2012; Hart et al 2016; Brewer et al 2019; Forrest et al 2019; Alsos et al 2020; Bakker et al 2020; Folk et al 2021; Kates et al 2021). In addition, target capture sequencing of leaves generates a considerable sequence bycatch in the form of off-target reads (‘genome skimming’) that represent a wealth of chloroplast genes, allowing simultaneous reconstruction of the plastome (Weitemier et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One would expect that plants collected and desiccated in cool and dry environments would yield higher quantities of less‐degraded DNA than plants collected under wet and tropical conditions. Although thus far only a few studies have tried to investigate these aspects (e.g., Kates et al, 2021 ), Bakker et al ( 2016 ) found that, based on read assembly results, the fragmentation effects caused by the age of the sample were more consistent in materials from wet and tropical environments, probably due to the longer and more destructive preparation methods used (e.g., heat, alcohol).…”
Section: Discussionmentioning
confidence: 99%
“…These proportions are comparable to those obtained using the same kit with fresh (silica gel–dried) samples (data not published). The target enrichment has already been successfully applied to relatively old herbarium specimens (Hart et al, 2016 ; Villaverde et al, 2018 ; Kates et al, 2021 ); however, for very old specimens (>200 years), methods based on genome skimming and the assembly of multicopy genome regions (e.g., organellar DNA), coupled with single‐stranded DNA library preparation, perform better than the target enrichment of single‐copy nuclear regions (Bakker, 2017 ). Our results confirm the potential of the latter technique, even when applied to herbarium specimens up to 200 years old.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA sequence data used here were extracted from the set of 100 low-copy nuclear loci used in a project (Folk et al 2021a; Kates et al 2021) that sampled ca. 15,000 species of the nitrogen-fixing clade of angiosperms, of which Fagales are a part.…”
Section: Methodsmentioning
confidence: 99%